A High Rate of Alternative Diagnoses in Patients Referred for Presumed Clostridium difficile Infection. Issue 9 (October 2016) - Jackson, Melissa; Olefson, Sidney; Machan, Jason T.; Kelly, Colleen R.
Abstract : Goals: We evaluated a cohort of patients referred to our center for presumed recurrent Clostridium difficile infection (CDI) to determine final diagnoses and outcomes. Background: As rates of CDI have increased, more patients are diagnosed with recurrent CDI and other sequelae of the infection. Distinguishing symptomatic patients with CDI from those who are colonized with an alternative etiology of diarrheal symptoms may be challenging. Materials and Methods: We performed a retrospective review of 117 patients referred to our center for recurrent CDI between January 2013 and June 2014. Data collected included demographics, the referring provider, previous anti-CDI treatment, and significant medical conditions. In addition, we gathered data on atypical features of CDI and investigations obtained to investigate the etiology of symptoms. Outcomes included rates of alternative diagnoses and the accuracy of CDI diagnosis by the referral source. Results: The mean age was 61 years, and 70% were female. About 29 patients (25%) were determined to have a non-CDI diagnosis. Most common alternative diagnoses included irritable bowel syndrome (18 patients: 62%) and inflammatory bowel disease (3 patients:10%). The age was inversely correlated with the rate of non-CDI diagnosis ( P =0.016). Of the remaining 88 (75%) patients with a confirmed diagnosis of CDI, 25 (28%) received medical therapy alone and 63 (72%) underwent fecal microbiota transplantation. Conclusions: Among patients referred to our center for recurrent CDI, a considerable percentage did not have CDI, but rather an alternative diagnosis, most commonly irritable bowel syndrome. The rate of alternative diagnosis correlated inversely with age. Providers should consider other etiologies of diarrhea in patients presenting with features atypical of recurrent CDI.